Application of enzyme-producing bacteria for municipal solid waste biodegradation - Nailah, Sa’adah (2015)
Population growth with increasing consumption levels leads to abundant waste in Kuantan. Jabor landfill, commonly known as Kuantan landfill, receives more than 500 tons of waste per day with a composition of 60% of domestic waste and 40% of commercial waste. The composition of domestic waste were organic waste, green waste, mixed paper, plastic, textile, ferrous, glass, rubber and leather, and others. Meanwhile, the compositions of commercial waste are food, plastic, yard waste, paper, cardboard, textile, glass, non-ferrous, rubber, wood, ferrous metals. Landfill system always produces leachate. This waste contains many types of bacteria with the potential to degrade the waste compound. Screening tests with selective media demonstrated the ability of bacteria to produce amylase, lipase, protease and cellulase enzymes. These enzymes are needed to accelerate the molecules breakdown of municipal solid waste in the biodegradation process. Samples for isolation of bacteria were taken from different places, namely landfill soil and leachate. Identification of bacteria was conducted using Gen III microplate BIOLOG microbial identification system. They were Bacillus amyloliquefaciens, Bacillus ruris, Bacillus licheniformis, Bacillus subtilis and Kocuria varians. There were 4 different treatments: composting pile without bacteria (T0), composting pile with inoculation of amylase and protease producing bacteria (T1), composting with inoculation of lipase and cellulase producing bacteria (T2), and composting with inoculation all enzyme-producing bacteria (T3). The result of biodegradation process of T3 treatment reached the highest temperature (53° C) with the longest thermophilic phase compared to other treatments. The lower value of C/N ratio, the more stable the level of maturity of compost. The lowest of C/N ratio value was T3 (10%). T3 treatment compared with other treatments can increase as much as 27% content of nitrogen, 67% of phosphorus and 33% of potassium. All the treatments with bacterial inoculation (T1, T2, and T3) are able to reduce the content of heavy metals (Fe, Zn, Cu) on municipal solid waste biodegradation. It can be concluded that the inoculation of potential enzyme-producing of bacteria on municipal solid waste biodegradation is effective to increase the nutrient content and decrease the heavy metals.